Assessment of occupational exposure to stainless steel welding fumes – A human biomonitoring study. (1st September 2020) - Stanislawska, M.; Janasik, B.; Kuras, R.; Malachowska, B.; Halatek, T.; Wasowicz, W.
Highlights: The study was carried out in metal industry plants under real working conditions. Welding fumes and airborne metals were collected in the welders' breathing zone. Chromium, nickel and manganese were determined in biological samples. Effectiveness of biological monitoring was confirmed. Abstract: The aim of the study was to determine the concentration of hexavalent and trivalent chromium, nickel, manganese, and iron in welding fumes (WFs) and to evaluate the significant association between the concentration of metals in the biological material of welders. The studies were conducted in welders (n = 67) and controls (n = 52). Stainless steel WFs were continuously collected in the workers' breathing zone during a shift. The serum and urine concentrations of Cr and Ni were determined by ICP-MS. The content of Mn in the whole blood was determined using ET-AAS. The content of Cr in the erythrocytes was determined using ICP-MS. The Cr concentration in the welders' urine positively correlated with a work environment concentration of Cr (R = 0.59, p < 0.0001), Cr(VI) (R = 0.58, p < 0.0001), and Cr(III) (R = 0.64, p < 0.0001) in the inhalable fraction. The Ni concentration in the welders' urine positively correlated with the Ni concentration in the inhalable and respirable fraction (R = 0.34, p < 0.005 and R = 0.44, p < 0.002). The correlation between the Mn concentration in the work environment air and the Mn concentration in the welders' whole blood (R = 0.46, p < 0.0001) was observed.